The impact of electronic illiteracy on the scientific production of postgraduate students -A field study on a sample of doctoral students at the university of Mohamed khider biskra - أميرة سابق; سمير صالحي (International Journal of Social Communication, 2023)
Through this study, we aim to reveal a phenomnon that distuebs societies and hinders the progress of universities, which is strengthened by the products of its students and the quality of its outputs, which is electronic illiteracy and the inability to deal with technological means, which negatively affects the scientific production of students, especially graduate students, the study was conducted on a sample of doctoral students at the university of Mohamed kheidar biskra, and the negative impact of electronic illiteracy on scientific was emphasized, which necessitates fighing this phenomenon through various scientific demonstrations.